2011
DOI: 10.1007/s00066-011-2197-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemoradiation after laparoscopically assisted vaginal radical hysterectomy (LARVH) in patients with cervical cancer

Abstract: With similar oncologic outcome data and mostly mild side effects, LARVH followed by (chemo)radiation is a valid alternative in the treatment of cervical cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Our data support the assumption that this issue may be of special relevance in patients with pelvic lymph node metastases. Positive lymph nodes have been identified as main risk factor for local and distant relapse in this trial approved by others [17,8,34,14,11]. Also in a recently published trial, the survival benefit after radiochemotherapy was more prominent among patients with at least two positive nodes than in patients with only one nodal metastasis [26].…”
Section: Discussionmentioning
confidence: 91%
“…Our data support the assumption that this issue may be of special relevance in patients with pelvic lymph node metastases. Positive lymph nodes have been identified as main risk factor for local and distant relapse in this trial approved by others [17,8,34,14,11]. Also in a recently published trial, the survival benefit after radiochemotherapy was more prominent among patients with at least two positive nodes than in patients with only one nodal metastasis [26].…”
Section: Discussionmentioning
confidence: 91%
“…Physicians were reluctant to perform RH in patients with bulky early-stage cervical cancer based on these results. However, recent other reports found that the rates of serious toxicity were lower after RH+RT; the rate of toxicity of grades 3-4 was only 7%, being 2% and 3% in terms of gastrointestinal and genitourinary complications, respectively [13,16,25]. When we evaluated the occurrence of grade 3-4 toxicities that required treatment, we found that the rates of grade 3-4 early complications were not different between RH+RT group and CRT group (24.2% vs. 30.9%, p=0.342).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical squamous carcinoma (CSC) is the most common pathological type of UCC, accounting for 75-80% of the total number of cervical cancer patients [2]. Poorly differentiated CSCs can easily cause local invasion and distant metastasis, affecting the choice of treatment and prognosis of patients [3,4]. Therefore, it is important to accurately assess the grade of CSC before treatment.…”
Section: Introductionmentioning
confidence: 99%